Factors affecting the occurrence of sound matching (Eurasian Journal of Philology Science and Education, 2019)
The article deals with the diversity of speech being in accordance with the sounds that have arisen ina certain period of the history of language development. In this regard, its functions also relate to certainareas of the language. Sound matching is not only a work of a certain period, but also a General continuation of a certain language that was used before, as well as the development of a common language thatis presented as a time difference of the next era. It is not necessary to consider correspondence of thesounds which have reached our times as the phenomenon of one period.